-4h -6 = 22
To solve this, we need to get -4h by itself and then simplify.
-4h -6 = 22
Add 6 to both sides.
-4h = 28
Divide both sides by -4.
h = -7.
I hope this helps!
The expression 12(7x+48) is greater than (12x-3) +4(x+5)
As,
12(7x+48) = 84x+576 and,
(12x-3) +4(x+5) = 16x+2
∴ Its clearly shown that 84x+576>16x+2
Answer: $9.71
Step-by-step explanation: Just subtract the pizza amount (8.50) and the drink (1.79) from the $20.
The opposite of multiplication is division, so if you take the signaler number after the equal sign divide it by the number before and it will give you the missing number like this:
(I'm only going to do a few and then you try it. I can check it when you are done)
6 x ____ = 60 <<<Divide 6 by this number
60 ÷ 6 = 10
6 x 10 = 60
140 ÷ 10 = 14
140 = 14 x 10
500 ÷ 50 = 10
50 x 10 = 500
Hope this helps!